2021
DOI: 10.1038/s41598-021-88265-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluations of vortex vein ampullae by adjusted 3D reverse projection model of ultra-widefield fundus images

Abstract: The purpose of this study was to determine the number and location of vortex vein ampullae (VVA) in normal eyes. This was an observational retrospective study. Montage images of one on-axis and two off-axis ultra-widefield images of 74 healthy eyes were enhanced, and reverse projected onto a 3D model eye. The number and distance between the optic disc to each VVA in the four sectors were compared. The significance of correlations between these values and age, sex, visual acuity, refractive error, and axial len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Introducing new parameters, en-face p-CVD, and p-CVS, our study uncovered signi cant sex differences in choroidal structure, posteriorly and peripherally, surpassing CCT in distinguishing between sexes even after adjusting for confounders. These results align with our previous research indicating a greater number of vortex vein ampullas in men 25 and higher fundus tessellation, suggesting larger choroidal vessels in males. 26 Our study further supports the notion that quantitative measurements from wide-angle choroidal en-face images effectively capture sex differences in the choroid.…”
Section: Discussionsupporting
confidence: 93%
“…Introducing new parameters, en-face p-CVD, and p-CVS, our study uncovered signi cant sex differences in choroidal structure, posteriorly and peripherally, surpassing CCT in distinguishing between sexes even after adjusting for confounders. These results align with our previous research indicating a greater number of vortex vein ampullas in men 25 and higher fundus tessellation, suggesting larger choroidal vessels in males. 26 Our study further supports the notion that quantitative measurements from wide-angle choroidal en-face images effectively capture sex differences in the choroid.…”
Section: Discussionsupporting
confidence: 93%
“…Men reportedly have significantly thicker choroids than women [ 13 , 19 ], and reports exist on the sex differences in the lumen/interstitial ratio [ 13 ]. We examined the number of vortex vein ampullae from montage fundus images and reported that the mean number of vortex veins was significantly higher in men than in women, which was more pronounced in the superior quadrant [ 20 ]. The lower number of vortex veins in women could result in a higher blood return volume per each Haller vessel in women.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Therefore, the information on peripheral choroidal vessels collected by ICGA is limited, and it is practically challenging to compare pachychoroidal images with normal ones, which have many variations. 20 , 21 , 22 Furthermore, when examining the location of peripheral choroidal vessels, it is difficult to capture the entire fundus even with an ultrawide-field fundus image. Distortion makes strict quantitative evaluation difficult even if a montage image is created.…”
mentioning
confidence: 99%
“…Distortion makes strict quantitative evaluation difficult even if a montage image is created. 20 , 21 …”
mentioning
confidence: 99%
See 1 more Smart Citation